2020
DOI: 10.1111/jtxs.12573
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between polypharmacy, xerostomia, gustatory sensitivity, and swallowing complaints in the elderly: A multidisciplinary approach

Abstract: Oral dysfunctions are common in the elderly but the literature lacks a multidisciplinary approach on the relationship between polypharmacy, saliva flow, xerostomia, taste, and swallowing complaints. This cross‐sectional study included 204 non‐institutionalized elderly (>60 years; 123 women/81 men), free of severe disabilities and non‐alcohol/tobacco consumers, from whom specific pharmacological therapies were evaluated, as well xerostomia (Xerostomia Inventory‐XI) and swallowing complaints (EAT‐10 questionnair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 49 publications
1
15
1
1
Order By: Relevance
“…At the same time, it should be mentioned that we did not show differences in reported complaints between patients who underwent different types of care. This is consistent with previously published work [ 26 ]. Therefore, it should be understood that the oral health of elderly patients in an institutionalized 24-h care is poor and tends to deteriorate already before they are admitted to this type of facility [ 27 ].…”
Section: Discussionsupporting
confidence: 94%
“…At the same time, it should be mentioned that we did not show differences in reported complaints between patients who underwent different types of care. This is consistent with previously published work [ 26 ]. Therefore, it should be understood that the oral health of elderly patients in an institutionalized 24-h care is poor and tends to deteriorate already before they are admitted to this type of facility [ 27 ].…”
Section: Discussionsupporting
confidence: 94%
“…We observed self-reported xerostomia as it was a condition frequently observed (71%) in our sample. Castelo and colleagues [9] also showed a statistically significant correlation between OD and the presence of xerostomia using the EAT-10 questionnaire (ρ = 0.26; p < 0.001). Such association reveals the importance of salivation for an adequate formation of the food bolus, which takes place in the first phase of swallowing (oral), and is perceived by the patient as an effort to swallow.…”
Section: Discussion/conclusionmentioning
confidence: 92%
“…This study identified OD in 21% of the outpatient older adults using the EAT-10 questionnaire and V-VST, which is similar to previously published studies. Fernandes et al [9] also reported a prevalence of 20% in older adults. On the other hand, the presence of malnutrition was the only biological correlate identified for OD.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Quantitative and qualitative changes in salivary secretion can affect the oral health. In patients with chronic diseases and/or receiving pharmacological treatment, one of the most commonly reported complaints is dry mouth, 6 which has two aspects: xerostomia (subjective) and hyposalivation (objective), 7 which are not always correlated. In younger adults, hyposalivation was associated with BMI > 25 (obesity), while in those older than 50 years hyposalivation was associated with medication use 8 .…”
Section: Introductionmentioning
confidence: 99%